Sustainable Bacterial Control of Hatching Eggshells Using Essential Oils - Igor Rafael Ribeiro Vale; Gabriel da Silva Oliveira; Luana Maria de Jesus; Marcio Botelho de Castro; Concepta McManus; Vinícius Machado dos Santos (MDPI AG, 2024)
Background: Decontamination of poultry surfaces through appropriate hygiene and sanitation measures can partially mitigate bacterial problems, as this process does not result in the complete elimination of bacteria. Thus, the remaining bacteria can persist and contaminate eggshells. Therefore, regardless of the rigor of the sanitary standards applied on farms, it is suggested that hatching eggs be subjected to the sanitization process. Here, we investigated the effectiveness of essential oil-based antibacterial agents in sanitizing eggs. Results: The results indicated that essential oils from Cinnamomum cassia (L.) J. Presl. (CCEO), Syzygium aromaticum (L.) Merr. & L.M. Perry (SAEO) and Cymbopogon nardus (L.) Rendle (CNEO), at specific concentrations, have antibacterial effects in vitro, reducing the load of mesophilic bacteria and enterobacteria in the eggshell by at least 3 and 2 log10 CFU/mL, respectively. Conclusion: The adoption of CCEO, SAEO and CNEO to reduce the bacterial load on eggshells could be a favorable change to the conventional protocol of egg sanitization with formaldehyde, especially on farms where sanitary standards are insufficient.